PERLINDUNGAN TERHADAP KESELAMATAN PEKERJA DI PT TELEKOMUNIKASI Tbk DENPASAR - Agnis Ratna Dewi, Ni Nyoman; Nyoman Agung, I Gusti; Sandhi Sudarsana, I Ketut (Kertha Desa; Vol. 01, No. 01, Maret 2013, 2013)
Work is very important in human life that all people need jobs. Company in itscourse require human resources to support the effort. The application of technology inorder to avoid some of the preparation work accident. Occupational Safety protectionis set under Indonesian law. But there are still a lot of accidents are found in thecompany, due to factors that affect. The factors of the legislator, executor, orstakeholders. That the application of laws and regulations on the protection of workers'safety is in fact not been effectively implemented.
Keywords: Application, Safety Protection, Factorr, workers.